Dual vocational education and training systems in Europe facing similar challenges : approaches towards reform in Austria and Denmark - Le Mouillour, Isabelle [Verfasser] (My University, 2017)
"The aim of the European Erasmus+ Project “Apprenti-ceship Toolbox” was to present dual training systems in Europe. Within the scope of the project, it became clear that these systems are facing similar challenges. This article presents the challenges and approaches towards reform developed in Austria and Denmark." (author's abstract ; BIBB-Doku)
Duale Berufsbildungssysteme in Europa vor ähnlichen Herausforderungen
Keywords: I 2.2.1 Westeuropa; S 1.3.1 Ausbildung im Dualen System; Erasmus plus; Berufsbildungssystem; Duales System; Österreich; Dänemark